DISSIPATION OF ATRAZINE IN ALFISOLS AND SWEET CORN - T. RAMPRAKASH; YAKADRI M; M. MADHAVI (The Bioscan, 2015)
A field experiment was conducted in the College Farm, Rajendranagar, Hyderabad to study the persistence in soils and residual effects of atrazine in sweet corn during rainy season (Kharif) 2012 and 2013. Atrazine was applied as pre-emergence and post-emergence spray at two levels (1.0 and 2.0 kg/ha) and persistence was studied in soils (0, 10, 30, 45, 60 days after application, DAA, and harvest), maize grain/stover at harvest. Atrazine residue were determined using GC-NPD. In pre-emergence treatments, atrazine residues persisted in the soil upto 60 DAA at 1.0 and 2.0 kg/ha dose of application during both years. Atrazine residues concentration in the soil was lower in post-emergence treatments and residues persisted upto 45 DAA during two years at 1.0 kg and 2.0 kg/ ha application rates. Residues of atrazine in sweet corn grain and stover were below the detection during two years at two rates of application. Atrazine persistence insoil followed first order kinetics with half-life varying from 26.45 days to 35.77 days. Atrazine can be safely applied to sweet corn as the grain and stover residues were below the MRL values.